Guidelines for Developing Water Tourism Models in Chiang Rai Province to Accommodate Generation Y Tourists - Poomvichchuvech, Duangsiri; Saokham, Monsicha; Wongpatum, Numkwan; Yolthasart, Suraychanee (Parichart Journal, 2025)
The study on “Guidelines of Developing Water Tourism Models in Chiang Rai Province to Accommodate Generation Y” aimed to 1) study the behavior of water tourism activity selection, 2) examine the potential of water tourism operators, and 3) create guidelines for developing water tourism models in Chiang Rai. The study used a mixed method approach with the data collected from 400 generation Y Thai tourists. Questionnaires data was analyzed using the ordered logistic regression technique. Qualitative data was collected through focus group discussions with 30 stakeholders. The qualitative data was analyzed using the content analysis method. The study revealed the following findings. 1) Most of the samples traveled by private car with their families and were most interested in rafting activities. 2) Enhancing entrepreneurial potential involved considering the marketing mix that influenced service selection, including river ambiance, equipment rental prices, convenience of payment, communication methods, service rates, and resting areas. The results of the hypothesis testing showed that different water tourism behaviors affected the marketing mix in various aspects. 3) The guidelines for developing water tourism models should be executed through social media marketing strategies that enhance attractiveness and travel experiences, facilitate real-time booking, and prioritize safety, service quality, and environmentally sustainable tourist activities.Moreover, enhancing transportation infrastructure and accommodations will make tourist attractions more accessible.